C60 12–LEAD POST–ROSC ELECTROCARDIOGRAM DISCRIMINATES SURVIVAL TO HOSPITAL DISCHARGE. A SUB–ANALYSIS OF THE PEACE STUDY. (18th May 2022) - Gentile, F; Baldi, E; Schnaubelt, S; Caputo, M; Clodi, C; Bruno, J; Compagnoni, S; Benvenuti, C; Domanovits, H; Burkart, R; Primi, R; Ruzicka, G; et al.
Abstract: Background: Once the return of spontaneous circulation (ROSC) after an out–of–hospital cardiac arrest (OHCA) is achieved in patients with an ST–elevation myocardial infarction, the acquisition of a 12–lead electrocardiogram (ECG) is strongly recommended in order to determine candidates for urgent coronary angiography. However, little is known so far about the association of ECG features and survival to hospital discharge in OHCA patients. Methods: We analysed all the post–ROSC ECGs collected from January 2015 to December 2018 in three European centres (Pavia, Lugano and Vienna). For every ECG, the main features were analysed and filed in the database together with the pre–hospital data collected for every patient according to the Utstein style. Results: We collected 370 ECGs: 287 males (77.6%); median age 62 years old (IQR 53–70 years); 121 from Pavia (32.7%), 38 from Lugano (10.3%) and 211 from Vienna (57.0%). In Cox univariable regression, age older than 62 years [HR 1.7 (95% IC 1.1–2.4), p = 0.007], QRS wider than 120 msec [HR 1.87 (95% IC 1.3–2.7), p < 0.001], ST elevation in more than one segment [HR 1.7(95% IC 1.2–2.5), p=0.003], the presence of left bundle branch block (LBBB) [HR 1.7 (95% IC 1.1–2.9), p = 0.03] and a right bundle branch block [HR 1.8 (95% IC 1.1–2.8), p = 0.01] were all associated with death before hospital discharge. In multivariable Cox regression, adjusted for the ROSC–to–ECG time, age older than 62 years [HR 1.6 (95% IC 1.1–2.3), p = 0.01], QRS wider than 120 msec [HR 1.7 (95%IC 1.2–2.5), p = 0.004] and the presence of ST elevation in more than one segment [HR 1.7 (95%IC 1.2–2.5), p = 0.004] were independently associated with death before hospital discharge. By considering these latter three risk factors, the rate of survival to hospital discharge was significantly influenced by their number [no risk factor: 80.8%; 1 factor: 71.2%; 2 factors: 61.9%; 3 factors: 34.4%; p < 0.001, p for trend <0.001]. With a Cox regression model, considering the absence of risk factor as a reference, we confirmed that having 2 or 3 risk factors was significantly associated with death before hospital discharge [HR 1.9 (95%IC 1–3.5), p = 0.037 e HR 5.1(95%IC 2.6–10.1), p < 0.001 respectively]. Conclusions: Our study confirms the central role of ECG in STEMI patients resuscitated after an OHCA and proves that post–ROSC ECG features can be used for both the selection of patients who may benefit from urgent coronary angiography as well as for prognostic stratifications.